2018
DOI: 10.1051/0004-6361/201832691
|View full text |Cite
|
Sign up to set email alerts
|

The nature of molecular cloud boundary layers from SOFIA [O I] observations

Abstract: Context. Dense highly ionized boundary layers (IBLs) outside of the neutral Photon Dominated Regions (PDRs) have recently been detected via the 122 and 205 μm transitions of ionized nitrogen. These layers have higher densities than in the Warm Ionized Medium (WIM) but less than typically found in H II regions. Observations of [C II] emission, which is produced in both the PDR and IBL, do not fully define the characteristics of these sources. Observations of additional probes which just trace the PDRs, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…On the other hand, as C + is emitted only in regions where star formation is taking place, the molecular gas not illuminated by stars would be undetected. Finally, [C ii] emission is also found in the outer parts of nearby galaxies, where low-density H ii regions were reported to contribute up to ∼50% of the extended [C ii] emission (Madden et al 1993; see also Langer et al 2016Langer et al , 2018 for their studies of the Milky Way). More recently, [C ii] emission has also been observed in the outer parts of high-redshift SFGs (Fujimoto et al 2019;Ginolfi et al 2020b).…”
Section: Molecular Gas Mass Estimatesmentioning
confidence: 93%
“…On the other hand, as C + is emitted only in regions where star formation is taking place, the molecular gas not illuminated by stars would be undetected. Finally, [C ii] emission is also found in the outer parts of nearby galaxies, where low-density H ii regions were reported to contribute up to ∼50% of the extended [C ii] emission (Madden et al 1993; see also Langer et al 2016Langer et al , 2018 for their studies of the Milky Way). More recently, [C ii] emission has also been observed in the outer parts of high-redshift SFGs (Fujimoto et al 2019;Ginolfi et al 2020b).…”
Section: Molecular Gas Mass Estimatesmentioning
confidence: 93%
“…The pillar so formed is supported against radial collapse by magnetic field but undergoes longitudinal erosion by stellar winds and radiation. There exist multiple analytical (Bertoldi 1989;Bertoldi & McKee 1990) and numerical models (Lefloch & Lazareff 1994;Bisbas et al 2011), which explain and reproduce many of the observed features of these structures sculpted by the radiation and wind from massive O/B stars starting from either an isolated or an embedded pre-existing dense clump or core. Additionally, there are observations which find the presence of sequential star formation in such structures consistent with triggered formation of stars due to the photoionization-induced shocks (Sugitani et al 2002;Ikeda et al 2008).…”
Section: Introductionmentioning
confidence: 99%